2020
DOI: 10.21037/tau.2019.06.01
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of lymphadenectomy for bladder cancer: why, when, and how

Abstract: Radical cystectomy (RC) represents a standard treatment for non-metastatic muscle-invasive and select high-risk non-muscle invasive bladder cancer. Lymphadenectomy performed at time of RC identifies nodal metastases in up to 25% of patients despite normal imaging. There has been an increasing utilization of pelvic lymph node dissection (PLND) with RC since 1950, and in fact lymph node dissection is now recommended in contemporary National Comprehensive Cancer Network (NCCN) guidelines. Benefits of removing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 87 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Multiple retrospective studies have demonstrated a survival advantage when more, compared with fewer, LNs are removed [1] , [2] . Multiple potential mechanisms for the improvement in outcomes with higher LN yield have been proposed: (1) a direct therapeutic benefit of removal of cancerous LNs; (2) modification of treatments and earlier intensification of adjuvant treatments on identification of pN+ disease; and (3) LN yield acting as a surrogate marker for surgeon or institutional factors associated with a higher quality of care across the disease continuum [3] . While the effect of these factors on patient survival is a matter of debate, the influence of stage migration, also known as the Will Rogers effect, is an often-underappreciated and yet simpler (and arguably more likely) explanation of these findings.…”
mentioning
confidence: 99%
“…Multiple retrospective studies have demonstrated a survival advantage when more, compared with fewer, LNs are removed [1] , [2] . Multiple potential mechanisms for the improvement in outcomes with higher LN yield have been proposed: (1) a direct therapeutic benefit of removal of cancerous LNs; (2) modification of treatments and earlier intensification of adjuvant treatments on identification of pN+ disease; and (3) LN yield acting as a surrogate marker for surgeon or institutional factors associated with a higher quality of care across the disease continuum [3] . While the effect of these factors on patient survival is a matter of debate, the influence of stage migration, also known as the Will Rogers effect, is an often-underappreciated and yet simpler (and arguably more likely) explanation of these findings.…”
mentioning
confidence: 99%